Long non‐coding RNAs and prostate cancer - Misawa, Aya; Takayama, Ken‐ichi; Inoue, Satoshi (Cancer science, 2017)
Long non‐coding RNAs (lncRNAs) are RNA transcripts larger than 200 nucleotides that do not code for proteins the aberrant expression of which has been documented in various types of cancer, including prostate cancer. Lack of appropriate sensitive and specific biomarkers for prostate cancer has led to overdiagnosis and overtreatment, making lncRNAs promising novel biomarkers as well as therapeutic targets for the disease. The present review attempts to summarize the current knowledge of lncRNA expression patterns and mechanisms in prostate cancer, which contribute to carcinogenesis. In particular, we focused on lncRNAs regulated by androgen receptor and expressed in castration‐resistant prostate cancer. Long non‐coding (Lnc) RNAs modulate key cellular processes in normal physiology and diseases such as cancer. In this review, expression patterns of lncRNAs in prostate cancer and mechanisms which contribute to prostate carcinogenesis have been summarized.